2010
DOI: 10.1007/s12206-010-0707-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thickness and surface roughness on mechanical properties of aluminum sheets

Abstract: The effect of thickness on the mechanical properties of Al 6K21-T4 sheet specimens under uniaxial tension was investigated. In order to reduce the thickness of the specimens without changing the microstructure and grain size, chemical etching was carried out, resulting in Al sheets ranging from 0.40 mm to 1.58 mm in thickness. Additionally, the effect of surface roughness was determined by finite element (FE) calculations performed using FE code MARC 2007. Tensile specimens of varying surface roughness were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 16 publications
3
19
0
1
Order By: Relevance
“…7, the true fracture strain of the ARB-processed foils increases from 0.4 to 1.5 after two AR passes. At this point, the tensile stress increases by 21% and the ductility of the foils is much greater than that Fig.11-Thickness size effect during tensile process, (a) for Al 6K21-T4 with coarse grains, [48] (b) for annealed pure Cu foils, [8] and (c) for the samples in current experiments.…”
Section: Thickness Size Effect In Nanostructured Laminate Foilsmentioning
confidence: 72%
See 2 more Smart Citations
“…7, the true fracture strain of the ARB-processed foils increases from 0.4 to 1.5 after two AR passes. At this point, the tensile stress increases by 21% and the ductility of the foils is much greater than that Fig.11-Thickness size effect during tensile process, (a) for Al 6K21-T4 with coarse grains, [48] (b) for annealed pure Cu foils, [8] and (c) for the samples in current experiments.…”
Section: Thickness Size Effect In Nanostructured Laminate Foilsmentioning
confidence: 72%
“…As shown in Fig. 11a, [48] for annealed Al 6K21-T4 sheets of grain size 40 m, as the thickness of the sheet is reduced from 1600 m to 400 m, the engineering fracture strain is reduced from 0.25 to 0.15 and the tensile stress also decreases slightly. A similar phenomenon was also observed by Simons et al [8] who carried out tensile tests on thin rolled & annealed copper foils of different thicknesses.…”
Section: Thickness Size Effect In Nanostructured Laminate Foilsmentioning
confidence: 88%
See 1 more Smart Citation
“…That is to say, when a decreases, the effect of the surface on the mechanical properties is enhanced. Suh et al [46] found that the tensile strengths of Al 6K21-T4 sheets decreased almost linearly with thickness reduction when the thickness was reduced below a critical value. The previous discussion on the effect of different parameters on the material strength, such as deformation of secondary phase particles, sheet thickness, precipitation and reduction, can be expressed in the form of Eq.…”
Section: Strength Of As-rolled and Aged Sheetsmentioning
confidence: 99%
“…There is no significant difference for the ratio between the gauge length to gauge width between the ECAP and HPT tensile specimens and the major difference is the specimen thickness. It was reported that the yield and tensile strengths decreased when the number of grains over the thickness was decreased and the ductility also decreased when reducing the thickness [23,24]. Obviously considering the effect of specimen thickness on mechanical properties, it is reasonable to assume that specimen size has certain contributions to the low elongations in HPT processed AZ31 at 623 and 673 K with different test strain rates.…”
Section: Discussionmentioning
confidence: 99%